Individual, Social, and Environmental Correlates of Healthy and Unhealthy Eating. (December 2015) - Trapp, Georgina S. A.; Hickling, Siobhan; Christian, Hayley E.; Bull, Fiona; Timperio, Anna F.; Boruff, Bryan; Shrestha, Damber; Giles-Corti, Billie
Background. Few studies use comprehensive ecological approaches considering multilevel factors to understand correlates of healthy (and unhealthy) dietary intake. The aim of this study was to examine the association between individual, social, and environmental factors on composite measures of healthy and unhealthy dietary intake in adults. Method . Participants ( n = 565) of the Australian RESIDential Environments (RESIDE) project self-reported dietary intake, home food availability, and behavioral and perceived social and physical environmental inﬂuences on food choices. A geographic information system measured proximity of supermarkets from each participant's home. "Healthy" and "unhealthy" eating scores were computed based on adherence to dietary guidelines. Univariate and multivariate models were constructed using linear regression. Results. After full adjustment, "healthy" eating (mean = 6.25, standard deviation [ SD ] = 1.95) was significantly associated with having confidence to prepare healthy meals (β = 0.34; 95% confidence interval [CI] = [0.13, 0.55]); having more healthy (β = 0.13; 95% CI = [0.09-0.16]) and fewer unhealthy (β = −0.04; 95% CI = [−0.06, −0.02]) foods available at home; and having a supermarket within 800 meters of home (β = 1.39; 95% CI = [0.37, 2.404]). "Unhealthy" eating (mean = 3.53, SD = 2.06) was associated with being male (β = 0.39; 95% CI = [0.02, 0.75]), frequently eating takeaway (β = 0.33; 95% CI = [0.21, 0.46]) and cafe or restaurant meals (β = 0.20; 95% CI = [0.06, 0.33]) and having fewer healthy (β = −0.07; 95% CI = [−0.10, −0.03]) and more unhealthy (β = 0.09; 95% CI = [0.07, 0.10]) foods available within the home. Conclusion . Initiatives to improve adherence to dietary guidelines and reduce the consumption of unhealthy foods needs to be multifaceted; addressing individual factors and access to healthy food choices in both the home and neighborhood food environment. Ensuring proximity to local supermarkets, particularly in new suburban developments, appears to be an important strategy for facilitating healthy eating.